Prasanthi Ganapathy Ram. Nine Yard Sarees: A Short Story Cycle. Singapore: Ethos Books, 2024. 272 pp. ISBN 978-981-18-6035-5. - Singh, Tejash Kumar (SARE: Southeast Asian Review of English, 2024)
Precious little has been written on the Singaporean Indian diasporic life from a literary perspective. Writers such as Balli Kaur Jaswal have covered the Punjabi-Sikh diaspora, gleaning greater insights into the realities of a minority within a minority. Prasanthi Ganapathy Ram's Nine Yard Sarees adds onto this growing corpus by covering a multigenerational Tamil Brahmin family’s life, especially focusing upon the narratives and perspectives of Indian women across different time periods and spaces. Written across 1950 to 2019, Ram's short stories encapsulate the lived realities of nine women as they travel globally. Salient themes revolving the various Indian female perspectives are portrayed, such as migration and displacement, across others. Weaving together their interlinked stories in a richer portrayal of diaspora, Ram's strength lies primarily in her capturing of the nuances and complexities surrounding each female's perspective. Hence, her writing functions as a form of resistance against seeing the lived realities of females within the Indian diaspora in Singapore as a comfortable, homogeneous whole.